2018
DOI: 10.3390/ijms19092778
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Insulin Resistance and the Adipocyte-Skeletal Muscle Cell Cross-Talk by LCn-3PUFA

Abstract: The cross-talk between skeletal muscle and adipose tissue is involved in the development of insulin resistance (IR) in skeletal muscle, leading to the decrease in the anabolic effect of insulin. We investigated if the long chain polyunsaturated n-3 fatty acids (LCn-3PUFA), eicosapentaenoic and docosapentaenoic acids (EPA and DPA, respectively) could (1) regulate the development of IR in 3T3-L1 adipocytes and C2C12 muscle cells and (2) inhibit IR in muscle cells exposed to conditioned media (CM) from insulin-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…We demonstrated that DNA methylation is an essential component of IR pathogenesis in adipose tissue. The IR was induced in experimental cells: 3T3-L1 adipocytes and human adipocytes collected from SAT and VAT by palmitic acid, which is one of the most common methods used by numerous researchers [22,23]. We successfully induced IR both in 3T3-L1 and human adipocytes, which was confirmed by a glucose uptake assay.…”
Section: Discussionmentioning
confidence: 56%
“…We demonstrated that DNA methylation is an essential component of IR pathogenesis in adipose tissue. The IR was induced in experimental cells: 3T3-L1 adipocytes and human adipocytes collected from SAT and VAT by palmitic acid, which is one of the most common methods used by numerous researchers [22,23]. We successfully induced IR both in 3T3-L1 and human adipocytes, which was confirmed by a glucose uptake assay.…”
Section: Discussionmentioning
confidence: 56%
“…An in vitro model of palmitate-induced insulin resistant 3T3-L1 adipocytes has been established to study obesity-associated complications, including insulin resistance [ 13 , 16 , 23 ]. Indeed, several studies have shown that concentrations of 0.2–0.75 mM palmitate are enough to induce insulin resistance in various cell lines over a 16–24 h period [ 11 , 24 ]. In our laboratory, we have explored metabolic alterations associated with palmitate-induced insulin resistance in 3T3-L1 adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…We evaluated them on the 3T3-L1 adipocytes, the most commonly studied cell model used as the adipose tissue model in cell culture to examine various types of metabolic disorders [ 33 , 34 ]. It responds to insulin similar to human adipocytes; as well, there are the same methods to induce resistance to insulin using the same chemical components [ 35 , 36 ]. Therefore, in the present study, we used palmitic acid to induce insulin resistance in mature 3T3-L1 adipocytes, which successfully developed resistance to insulin in experimental cells, proven by the insulin-stimulated glucose uptake measurements.…”
Section: Discussionmentioning
confidence: 99%